Some Thoughts About Accounting Conceptual Framework and Standards For Awqaf Institutions - Muhammad Akhyar Adnan; Maliah Sulaiman; Putri Nor Suad Megat Mohd Nor (Indonesian Management and Accounting Research, 2007)
The awqaf institutions are, perhaps the less developed Islamic financial institutions compared to banking, insurance and zakat. However, these institutions are numerous and widespread all over the world, particularly in the countries where Muslim population is in existence. The attention to awqaf institutional development just took place in the last three to five years back. It is perhaps, why the development of these institutions seemed to be left far behind than other Islamic institutions. It is undeniable that the hidden strengths of awqaf institutions in solving the problems of the ummah, such as education, health and poverty eradication are so promising. However, this power will not be possible to explore, unless a variety of efforts are done. Among the important aspects that are less considered are the accounting issues which are strongly related to transparency, accountability and good governance. Needless to say accounting is one of critical points must be linked in the muamalah and ibadah activities. Several verses of the Holy Qur'an [QS 2:282: 5:1; 17:35, to mention but few] clearly assert some values related to accounting. Despite of the urge raised by others (e.g. Shahul and lhsan, 2007; Adnan, 2005) to develop a specific accounting standards for awqaf institutions, and accounting standards process being carried out by AAQIFI (2006), the discussion about how the conceptual framework and accounting standards should be welcome. This paper offers some thoughts which are expected to contribute to the development of conceptual framework and accounting standards for awqaf institutions. The discussion will be based on some review on related existing accounting standards on charity organizations, integrated with Islam ic values that cannot be released by awqaf institutions.JEL Classification: M4; N45Keywords: Awqaf Institutions, Accounting, Conceptual Framework, Standards